The therapeutic activity of low-dose irradiation on experimental arthritis depends on the induction of endogenous regulatory T cell activity. Issue 8 (24th May 2010) - Weng, Ling; Williams, Richard O.; Vieira, Pedro L; Screaton, Gavin; Feldmann, Marc; Dazzi, Francesco
Abstract : Background: It has been widely demonstrated that a quantitative and/or qualitative impairment of regulatory T cells (Tregs ) play a fundamental role in the initiation and persistence of rheumatoid arthritis (RA) in animal models and in patients. In the present work it is demonstrated that partial myeloablation induces a relative expansion of Tregs that is sufficient to mediate immunological tolerance. Objectives: (1) To test the ability of low-intensity myeloablation mediated Treg activation to prevent and/or to treat experimental arthritis using the collagen-induced arthritis (CIA) model and (2) to clarify the role of Treg in mediating the beneficial effect. Methods: Low-dose irradiation was used before the induction of arthritis or at the onset of disease. The role of Tregs (CD4CD25forkhead box P3 (FoxP3) + cells) and their suppressive activity was assessed by testing their functional activities ex vivo after the treatment and by their in vivo depletion before the treatment. Results: It was observed that irradiation ameliorated CIA before or after disease induction. Tregs appear to play a fundamental role in the therapeutic efficacy of irradiation, because the depletion of CD25 or folate receptor (FR)4 + cells with specific antibodies before the treatment abolished the beneficial effects. The therapeutic efficacy was associated with an increment in the proportion of Tregs despite the overall reduction in lymphocyte counts. Furthermore, a decline in the percentage of CD4CD25FoxP3 + Tregs was associated with disease flare. Conclusion: In vivo Treg expansion is a feasible and effective approach in the treatment of autoimmune diseases.